Writing the wrongs : Eva Valesh and the rise of labor journalism - Faue, Elizabeth (Cornell University Press, 2002)
"Eva McDonald Valesh was one of the Progressive Era's foremost labor publicists. Challenging the narrow confines placed on women, Valesh became a successful investigative journalist, organizer, and public speaker for labor reform." "Valesh was a compatriot of the labor leaders of her day and the "right-hand man" of Samuel Gompers, president of the American Federation of Labor. Events she covered during her colorful, unconventional reporting career included the Populist revolt, the Cuban crisis of the 1890s, and the 1910 Shirtwaistmakers' uprising. She was described as bright, even "comet-like," by her admirers, but her enemies saw her as "a pest" who took "all the benefit that her sex controls when in argument with a man.""